The influence of Learning Techniques and Schemata Levels in Ability to Read English Academic Text - Marhany Malik; Emzir Emzir; Sabarti Akhadiah (STKIP Singkawang, 2017)
The aim of this study is to find out the effects of learning techniques and the levels of the schemata of the ability in reading English academic texts of Islamic Studies. This research was quasi-experimental, involved 60 samples of students of Tafsir-Hadis Departement, The first semester of 2012/2013 academic year. Faculty of Ushuluddin and Philosophy, UIN (State Islamic University) Alauddin Makassar. The finding that there is an interaction effect between learning techniques and the levels of the schemata of Islamic studies toward the students' ability in reading English academic texts.